2001
DOI: 10.1172/jci12156
|View full text |Cite
|
Sign up to set email alerts
|

LPS antagonism reduces graft-versus-host disease and preserves graft-versus-leukemia activity after experimental bone marrow transplantation

Abstract: Acute graft-versus-host disease (GVHD) and leukemic relapse remain the two major obstacles to successful outcomes after allogeneic bone marrow transplantation (BMT). Recent studies have demonstrated that the loss of gastrointestinal tract integrity, and specifically the translocation of LPS into the systemic circulation, is critical to the induction of cytokine dysregulation that contributes to GVHD. Using a mouse BMT model, we studied the effects of direct LPS antagonism on GVHD severity and graft-versus-leuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
207
2
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(215 citation statements)
references
References 47 publications
4
207
2
1
Order By: Relevance
“…Previous investigators have suggested that the mechanism of the actions of TNF during acute GVHD was as an effector of host cytotoxicity (9,43). More recent studies have demonstrated that the absence of TNFR1 on host cells was associated with a delay in mortality from acute GVHD, but had no effect on histologic patterns of GVHD in the intestinal tract or liver (42).…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigators have suggested that the mechanism of the actions of TNF during acute GVHD was as an effector of host cytotoxicity (9,43). More recent studies have demonstrated that the absence of TNFR1 on host cells was associated with a delay in mortality from acute GVHD, but had no effect on histologic patterns of GVHD in the intestinal tract or liver (42).…”
Section: Discussionmentioning
confidence: 99%
“…Lipopolysaccharide (LPS), a component of Gram-negative bacterial cell walls and a known agonist of Toll-like receptor 4 (TLR-4) (24), is considered a major marker of microbial translocation (25)(26)(27). In addition to local defense against microbial translocation at the level of the GI mucosa and within the liver, several lines of protection are active in the systemic circulation to neutralize translocating LPS and its downstream effects as a potent immune-activating molecule, thus limiting the detrimental effects of microbial translocation.…”
Section: Definition Of Microbial Translocationmentioning
confidence: 99%
“…During the early phase of GvHD LPS is a major pathogenic factor that enhances GvHD and leads to the activation of DCs. 37 Therefore, we evaluated the effects of Syk signaling in unstimulated and LPS-stimulated DCs. LPS enhanced expression of the costimulatory molecules CD80, CD86, CD40 and major histocompatibility complex class I and II.…”
Section: Pharmacologicalmentioning
confidence: 99%